Current knowledge of Epigenetic Events in Multiple Myeloma - Flodrova, Pavla; Luzna, Petra; Weiser-Drozdkova, Denisa; Trtkova, Katerina Smesny (New Frontiers in Medicine and Medical Research Vol. 5, 2021)
Multiple myeloma (MM) is a biologically heterogenic disease with adequate wide spectrum of chromosomal, genetic and epigenetic changes. Epigenetic modifications can influence gene activity without changing the DNA sequence. There are biochemical modifications that include DNA methylation and post-translational modification of histone proteins (histone methylation, histone acetylation and deacetylation), that play an important role in the pathogenesis of MM. Epigenetic modifications are mediated through very important specialized enzymatic molecules, e.g. DNA methyltransferases (DNMTs), ten-eleven translocation enzymes (TET), histone acetyltransferases (HATs) and histone deacetylases (HDACs). In a complex machinery, specific of micro-RNA molecules contribute to epigenetic processes. Not only in myeloma genesis, but epigenetics influences a drug resistance and prognosis of patients with MM as well.